Multiscale fluid–structure interaction modelling to determine the mechanical stimulation of bone cells in a tissue engineered scaffold - Feihu Zhao (Biomechanics and Modeling in Mechanobiology, 2015)
Recent studies have shown that mechanical stimulation, by means of flow perfusion and mechanical compression (or stretching), enhances osteogenic differentiation of mesenchymal stem cells and bone cells within biomaterial scaffolds in vitro. However, the precise mechanisms by which such stimulation enhances bone regeneration is not yet clear. The physical environment within a scaffold under perfusion is extremely complex and requires a multiscale and multiphysics approach to study the mechanical stimulation of cells. In this study, we aim to determine the mechanical stimulation of osteoblasts seeded in a biomaterial scaffold under flow perfusion and mechanical compression using multiscale modelling by twoway fluid–structure interaction and FE approaches. The mechanical stimulation, in terms of wall shear stress (WSS) and strain in osteoblasts, is quantified at different locations within the scaffold for cells of different morphologies (i.e. attached, bridged). The results show that 75.4% of scaffold surface has a WSS of 0.1–10 mPa, which indicates the likelihood of bone cell differentiation at these locations. For attached and bridged osteoblasts, the maximum strains are 397 and 177,200με, respectively. Additionally, the results from mechanical compression show that attached cells are more stimulated (maximum strain = 22, 600 με) than bridged cells (maximum strain = 10, 000 με). Such information is important for understanding the biological response of osteoblasts under in vitro stimulation. Finally, a combination of perfusion and compression of a tissue engineering scaffold is suggested for osteogenic differentiation.